Dynamika zmian powierzchni leśnych na terenie gminy Suchy Las w okresie 1940-2000 - Macias, Andrzej; Michalczyk, Aleksandra (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
The article presents the results of a research on the dynamics of change in the woodland area of Suchy Las commune in the 1940–2000 period. The commune was chosen because of its interesting spatial division resulting from the existence of the Biedrusko military ground within its limits. A comparison was made of the level of afforestation of the commune as provided by its topographic maps from the years 1940, 1960, 1980, and 2000. An analysis was also made of the number of woodland complexes as well as the extent of deforestation and afforestation. Throughout the study period the commune was divided into two characteristic spatial units. The lasting separation of functions and totally different land-use patterns has made them develop radically dissimilar landscapes. Over the study period the commune’s total woodland area grew from 23.75 ha to 43.5 ha, but in the military ground it increased from 24.45 ha to 42.04 ha, while beyond it there was a decline from 2.3 ha to 1.46 ha. The military ground in Suchy Las commune greatly restricts the possible uses of land there and reduces the area of potential investment by more than a half, but on the other hand such an extensive green space (the woodiness index for this part of the commune equals 36.1%) is its great natural wealth, enhances its landscape attractiveness, and facilitates natural vegetation growth. By contrast, the area outside the military ground features very sparse woodland (the woodiness index for this part of the commune is a mere 1.2%), which is due to the necessary concentration of many functions in a small area. The economic development of the commune may lead to further loss of woodland in this part.